Treatable traits in chronic rhinosinusitis with nasal polyps. Issue 4 (August 2019) - Heffler, Enrico; Malvezzi, Luca; Pirola, Francesca; Zięba, Natalia; Paoletti, Giovanni; Mercante, Giuseppe; Spriano, Giuseppe; Canonica, Giorgio Walter
Abstract : Purpose of review: Chronic rhinosinusitis with nasal polyps (CRSwNP) is a complex inflammatory sinonasal disease that deserves a multidisciplinary precision medicine approach. In a precision medicine model, a more pragmatic approach taking in consideration disease features that are potentially treatable should be considered. Recent findings: Several treatable traits in CRSwNP can be identified: from disease-related ones, to extra-ENT features, to behavioral and environmental factors. This review article summarizes primarily the recent findings of CRSwNP-related treatable traits and how they can be modified by given treatments. Summary: The advent of biological agents acting directly to the endotype underlying CRSwNP pushes the scientific community to integrate clinical, surgical and immunological evaluations for each single patient; this naturally leads to the identification of specific treatable traits that can serve as possible outcomes for any single biological.